2016
DOI: 10.21307/ane-2017-017
|View full text |Cite
|
Sign up to set email alerts
|

High-dose 1,25-dihydroxyvitamin D supplementation elongates the lifespan of Huntington's disease transgenic mice

Abstract: Huntington's disease is an autosomal dominant progressive neurodegenerative disease, which results in a decreased quality of life and an early death. A high prevalence of vitamin D deficiency was first described in a 2013 study in patients with manifest Huntington's disease, where serum vitamin D level was found to be associated with motor capabilities of the patients. Objectives: Our objective was to investigate the effect of a high-dose vitamin D3 supplementation on a transgenic mouse model of Huntington's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Thus, we paid a special attention to study design regarding the following points: we used the N171-82Q tg model of HD, because the phenotype of these mice mimics better the majority of human cases with considerable similarities in pathological alterations as well than the R6/2 tg mice, the symptoms of which mainly resemble that of juvenile HD cases. Furthermore, the authors have extensive previous experiences with this model [15,35,40,59,62,63,68,69], which enables the drawing of indirect correlations between the characteristic features of disease progression with the time course of the changes in mRNA expression patterns. Characteristically, in N171-82Q mice the symptoms begin to develop at approximately 2 months of age and disease progression results in a mean survival time of 110-130 days [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we paid a special attention to study design regarding the following points: we used the N171-82Q tg model of HD, because the phenotype of these mice mimics better the majority of human cases with considerable similarities in pathological alterations as well than the R6/2 tg mice, the symptoms of which mainly resemble that of juvenile HD cases. Furthermore, the authors have extensive previous experiences with this model [15,35,40,59,62,63,68,69], which enables the drawing of indirect correlations between the characteristic features of disease progression with the time course of the changes in mRNA expression patterns. Characteristically, in N171-82Q mice the symptoms begin to develop at approximately 2 months of age and disease progression results in a mean survival time of 110-130 days [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…A study of institutionalized HD patients found a high prevalence of VitD deficiency or insufficiency, and a positive association between calcifediol 25 (OH)D levels, an indicator of Vit D status, and ambulatory abilities was observed [221]. In a transgenic mouse HD model, supplementation of calcitriol significantly improved clinical symptoms and augmented the life span [249]. Thus, serum calcitriol is positively related to the treatment of HD.…”
Section: Vitamins In Huntington's Diseasementioning
confidence: 99%
“…Vitamin D (VD) deficiency/insufficiency is highly prevalent in HD patients (Chel et al, ; Loffredo & Bruin, ). Research on HD transgenic mice has found that VD supplementation beneficially influences the clinical features of the disease (Molnár et al, ). Importantly, VD receptors protect mitochondria optimal function and play a key role in protecting cells from OS (Ricca et al, ).…”
Section: Oxidative Stress and Mitochondria Dysfunction In Hdmentioning
confidence: 99%